PENGARUH OPTIMALIS PEMBELAJARAN ONLINE DAN PARTISIPASI MAHASISWA TERHADAP MOTIVASI BELAJAR ONLINE MAHASISWA TINGKAT II PENDIDIKAN EKONOMI UNIVERSITAS NUSANTARA PGRI KEDIRI - Hamidah, Roimatul; Permata, Citra Intan Harum; Surindra, Bayu; Irmayanti, Elis (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
Distance learning or online is an institution-based formal education, where separate learning groups and communication systems are used in interactions. Online learning was chosen as something supportive to use during a pandemic, especially during Covid-19. The purpose of writing this paper is to determine the effect of optimization of online learning and student participation on online learning motivation of students of economic education level II, Nusantara PGRI University Kediri. This type of research is quantitative research. There were a total of 16 students at level II who were used as samples in this study. The data were collected through a questionnaire instrument of the optimization of online learning variables, student participation and online learning motivation. The data analysis technique used multiple linear regression analysis accompanied by validation and reliability tests. The calculation process uses SPSS 23 version. The test results show that the optimization of online learning and student participation has a positive and significant effect on online learning motivation of Level II Economic Education students, Nusantara PGRI University Kediri. The factor that greatly influences the online learning motivation of Level II Economic Education students at Nusantara PGRI University Kediri is the Optimization of Online Learning.